Dual Roles of Supporting Electrolytes in Organic Electrosynthesis - Lilla G. Gombos; Joachim Nikl; Prof. Dr. Siegfried R. Waldvogel (ChemElectroChem, 2024)
Abstract Synthetic electro‐organic chemistry is advancing to a well‐established methodology in academic research and industry. The simple process control minimizes reagent waste and avoids using toxic and environmentally unfriendly redox agents, providing a feasible and sustainable alternative to conventional techniques. However, a fundamental disadvantage, is the necessity of ion‐conductive components within the electrolyte. The recovery of these supporting electrolytes, as well as simple product isolation, pose challenges for work‐up strategies. This review presents the following electrochemical protocols featuring a simple material‐ and resource‐saving strategy: the dual role of supporting electrolytes as conductivity enabling components and reagents or meditators. This review is the first to conclude and categorize dual role strategies for the supporting electrolytes. It may inspire electrochemists to advance the development and optimization of electrochemical synthesis protocols towards more material‐ and resource‐efficient reaction control.